PENGARUH DIFFERENTIATION STRATEGY, LEVERAGE, DAN SIZE TERHADAP GOING CONCERN PADA PERUSAHAAN MANUFAKTUR YANG TERDAFTAR DI BEI TAHUN 2012-2014 - Marieta Ariani (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2015)
The purpose of this research is !o analyze the influence of differentiation strategy, leverage, and size of going concern company during mantifactw•ing companies in BEI with periode 2012 until 2014. Research conducted obtained from financial reports and company annual on the site of indonesian stock exchange. Sample used is 36 company the manufacturing sector listed on BEI in the 2012-2014. The sampling technique used purposive sampling. This research used Multiple Llinier Regression Analysis. The results showed that partially differentiation strategy had a significant positive effect on going concern, leverage had significant negative effect on survival, and size had a significant positive effect on going concern. While the simultaneous business strategy, leverage, and size have a significant effect on the survival.